PERAN PARENTS TEACHERS MEETING (PTM) DALAM TUMBUH KEMBANG ANAK DI TK MONTESSORI, YOGYAKARTA - Claudia Des Intan Mujur; Elstudy Prestiwati Ndruru; Gregorius Ari Nugrahanta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the importance of collaboration between parents andteachers in supporting the growth and development of early childhood, especiallythrough formal communication forums such as Parents Teachers Meeting (PTM).The purpose of this study was to understand the role of PTM in supporting childgrowth and development in Montessori Kindergarten in Yogyakarta. This studyuses a descriptive qualitative approach. The subjects in this study were theprincipal, teachers, and parents of students, while the object was theimplementation of PTM and its impact on child development. Data collectiontechniques were collected through observation, in-depth interviews, anddocumentation. Data analysis was carried out using the Miles and Hubermanmodel. The results of the study showed that PTM was implemented in two forms,namely Classical PTM at the beginning of the school year to convey the schoolsgeneral program, and Individual PTM which is carried out every 1-2 months todiscuss the development of each child. This process allows collaboration indeveloping stimulation programs that are appropriate to the individual needs ofchildren, according to Montessori principles. The active involvement of parents inPTM has a positive impact on increasing independent behavior, learningparticipation, and synergy between home and school. However, severalchallenges such as uneven parental participation and time constraints remainobstacles. This study confirms that structured and child-oriented PTM can supportthe holistic development of early childhood. Strategies are recommended toincrease parental participation, such as the use of digital communication mediaand flexible scheduling.